A pathological and clinical study of 706 primary tumours of the ovary in the largest tertiary hospital in Ghana - Patrick Kafui Akakpo; Leonard Derkyi-Kwarteng; Richard Kwasi Gyasi; Solomom Edward Quayson; Simon Naporo; Jehoram Tei Anim (BMC Women's Health, 2017)
Abstract Background Ovarian tumours are a leading cause of death in Ghana. Even though geographical and racial differences exist in the frequency, types and age distribution of primary ovarian tumours, information about the clinical and pathological characteristics of ovarian tumours in Ghana and its neighboring countries is scanty. We determined the frequency, age distribution, histopathological types and clinical features of primary ovarian tumours diagnosed at the Korle-Bu Teaching Hospital in Ghana to aid in the management of patients. Method All pathology records of ovarian tumours diagnosed from January 2001 to December 2010 were reviewed. Histopathologically, tumours were classified according to the then World Health Organization 1999 classification. Biographical and clinical data of patients were also collected and entered into Epi-info to determine the frequency, age distribution and other clinical features of the types of ovarian tumour. Results Seven hundred and six ovarian tumours were studied. Germ cell tumours were the most common (41.9%), with mean age of occurrence being 30.7 years (SD 12.7), they were dominated by mature teratomas (39.2%). Surface epithelial tumours were second, and commonly occurred in women aged 35–44years, 77 (26.8%). Sex cord stromal tumours followed with mean age of occurrence of 40.2 years (SD 17.9). The most common malignant tumours were surface epithelial (52.1%) dominated by serous carcinomas with mean age 50.1 years. Most patients (47.7%) presented within 1 month of onset of symptoms, feeling a lower abdominal mass (38.5%). Conclusion The most common primary ovarian tumours in this study are Germ cell tumours, dominated by mature teratomas. Adenocarcinomas are mostly serous and occur in younger women compared to findings of other Western studies. The single most common malignant ovarian tumour in children and adolescents is Burkitt lymphoma. Patients who develop ovarian tumours have no specific symptoms or signs at presentation, to aid early diagnosis.